2015
DOI: 10.1111/jai.12696
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity on survival, daily food intake and growth of juvenile round goby Neogobius melanostomus (Pallas, 1814) from a brackish water system

Abstract: The growth response of juvenile round gobies was tested in various salinities to assess the potential performance of the species in widely differing salinities in the Baltic Sea and adjacent waters. An experimental approach analysed the survival, daily food intake and growth of juvenile Neogobius melanostomus from the brackish water region of the Kiel Canal, Germany. Round gobies (TL = 61.5 AE5.3 mm; n = 40) were fed ad libitum (diet = mysid shrimp; energy content = 4.7 cal per mg dry weight) at salinity level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…It was even introduced and is widely established in the Laurentian Great Lakes (Charlebois et al, 2001;Vanderploeg et al, 2002). Round goby can affect freshwaters as well as brackish ecosystems by its high invasive potential, including high reproductive effort, aggressiveness, high foraging activity and, among others, its role as a vector of parasites (Hempel and Thiel, 2015;Horkova and Kovac, 2014;Ondrackova et al, 2015;Vanderploeg et al, 2002). On the other hand, round goby can represent a significant part of the diet of other fish (Hensler et al, 2008;Vanderploeg et al, 2002).…”
Section: Mots-clés : Invasions Biologiques Poisson Gobiidae Eau Domentioning
confidence: 99%
“…It was even introduced and is widely established in the Laurentian Great Lakes (Charlebois et al, 2001;Vanderploeg et al, 2002). Round goby can affect freshwaters as well as brackish ecosystems by its high invasive potential, including high reproductive effort, aggressiveness, high foraging activity and, among others, its role as a vector of parasites (Hempel and Thiel, 2015;Horkova and Kovac, 2014;Ondrackova et al, 2015;Vanderploeg et al, 2002). On the other hand, round goby can represent a significant part of the diet of other fish (Hensler et al, 2008;Vanderploeg et al, 2002).…”
Section: Mots-clés : Invasions Biologiques Poisson Gobiidae Eau Domentioning
confidence: 99%
“…; Snyder et al . ; Hempel & Thiel ). Ponto–Caspian goby invasions have been attributed to shipping traffic (Roche et al .…”
Section: Introductionmentioning
confidence: 99%
“…As vigorous and adaptive invaders with high reproductive capacities, five species of Ponto-Caspian gobies (Neogobius melanostomus, Ponticola kessleri, Neogobius fluviatilis, Proterorhinus semilunaris and Babka gymnotrachelus) are presently colonizing European freshwaters, European coasts and the Great Lakes and its tributaries. They are expected to colonize the majority of freshwater and brackish temperate water bodies worldwide (Puntila et al 2013;Snyder et al 2014;Hempel & Thiel 2015). Ponto-Caspian goby invasions have been attributed to shipping traffic (Roche et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The aquaria (120 × 50 × 50 cm, filled to ~150 L [25 cm] with the same de-ionized tap water amended for aquarium use as in the tanks) were divided into three separate compartments, one compartment was for filtration and oxygenation and the other two compartments for the fishes (one for each species). The compartments for fishes were the same size (48 × 50 × 25 cm, ~60 L de-ionized tap water amended for aquarium use) with gravel as substrate and additional enrichment (round goby: plastic tubes based on Hempel and Thiel (2015); European perch: plastic plants based on Magnhagen (2012)). Each compartment held 6 fish of similar size from the same species (10 L water per fish).…”
Section: Experimental Set-upmentioning
confidence: 99%
“…The species, the native European perch (Perca fluviatilis) and the invasive round goby (Neogobius melanostomus), were chosen based on their prevalence in the Rhine, where secondary salinization via mine water emission is extant (Wisotzky et al 2018;Schulz and Cañedo-Argüelles 2019). Earlier studies have shown that both European perch (Overton et al 2008;Christensen et al 2019a) and round goby have a wide range of salinity tolerance (Karsiotis et al 2012;Hempel and Thiel 2015). Further, European perch has a higher standard metabolic rate, that is minimum metabolic rate needed to sustain life for a specified temperature, (Ern et al 2014;Christensen et al 2019b), and round goby has a lower standard metabolic rate (Behrens et al 2017) in brackish water compared to fresh water.…”
Section: Introductionmentioning
confidence: 99%